Isolation and identification of acetogenic bacteria obtained from deer rumen and their potential for methanogenesis inhibitor - Thalib, Amlius (Indonesian Animal Sciences Society, 2008)
Methanogenesis can be inhibited by various chemicals through different mechanism reaktion. The use of acetogenic bacteria as H2 sink is assumed to be a promising approach. Isolation and identification of acetogenic bacteria obtained from deer rumen had been conducted. Two types of media used for isolation were hydrogen-carbondioxide utilizing acetogens and carbonmonoxide utilizing acetogens. Identification of species of acetogens isolates was based on descriptions of morphology, Gram type, motility, bioreaction results, and oksygen requirement. The compositions of methane and volatile fatty acids (VFA) were determined on minimal media or added with sheep rumen liquid innoculated with pure isolates. The identification results showed that the isolate cultured on media of hydrogen-carbondioxide utilizing acetogens was Acetoanaerobium noterae and the ones cultured on media of carbonmonoxide utilizing acetogens was Acetobacterium woodii. Inoculumn of A. noterae and A. woodii could decreased the composition of methane resulted from substrate fermented by fresh rumen liquid of sheep (CRDF), that is culture of A. noterae added FPM and defaunator decreased methane production by 28.8% (P<0.01), while culture of A. woodii added microbe growth factors (FPM) and defaunator decreased methane production by 20.6% (P<0.05). Composition of VFA resulted from fibrous substrate fermented by inoculumn of CRDF with and without combined with cultures of A. noterae dan A. woodii were not significantly different except for culture of A. noterae combined with FPM and defaunator additives was higher than CRDF (P<0.05) (ie. 122.9 vs. 97.9 mM for total VFA and 73.43 vs. 68.37% for composition of acetic acid). It is assumed that isolates of A. noterae and A. woodii could be functioned as methanogenesis inhibitor according to Â the reaction of Â 2CO2 + 4H2 ==> CH3COOH + 2H2O by which reduction of CO2 with H2 producing CH4 can be inhibited or decreased. Their function as methanogenesis inhibitor would be more significant when they are combined with microbial growth factors and defaunator. Kata Kunci: Asetogenik-bacteria, Acetoanaerobium noterae, Acetobacterium woodii, deer, methane